(untitled) (Asian Journal of Social Science Studies, 2021)
The purpose of this study is to investigate the relationship between consumption value and consumption propensity and tourist satisfaction and to verify the mediating effect of consumption propensity on tourists visiting China. A total of 300 surveys were conducted from December 1, 2018, to January 30, 2019, Overall, 286 surveys were conducted for SPSS 23.0. The empirical results of this study are as follows. First, five sub-factors of the consumption value were selected: social value, functional value, epistemic value, emotional value, and conditional value. For consumption propensity, two sub-factors labeled practical propensity and others-conscious propensity were chosen. Tourist satisfaction was set to be a single factor. Second, as for the results of identifying the importance of sub-factors of the consumption value, the order was social value, functional value, epistemic value, emotional value, and conditional value. Third, the relationship between the consumption value and tourist satisfaction showed that all factors of consumption value had a significant positive effect on tourist satisfaction. Fourth, the result of examining the relationship between the consumption value and consumption propensity showed that the factor of consumption value such as social value, functional value, epistemic value, the emotional value had a significant positive effect on tourist satisfaction while the conditional value had not, and all five factors of consumption value and others-conscious propensity had significant positive regression weight. Fifth. the result of checking the relationship between the consumption propensity and tourist satisfaction showed that all factors of consumption propensity had a significant positive effect on tourist satisfaction. Sixth, the analyses of mediating effect revealed as follows; the relationship between consumption value and tourist satisfaction was partially mediated by four factors, functional, emotional, epistemic, social, of the practical propensity of consumption propensity; and the relationship between consumption value and tourist satisfaction was partially mediated by all factors, of the others-conscious propensity of consumption propensity.